AC Losses in High-Temperature Superconductor Tapes and Cables for Power Applications - Godfrin, Aurélien (Karlsruher Schriftenreihe zur Supraleitung, 2022)
This work focuses on two topics. The first is the investigation of producing filaments on copper-stabilized coated conductors, with striations made after or before electroplating the tape. The second topic is the applicability of the striations for reducing the AC losses of cables, in particular the CORC® and RACC cables, which are made with high-temperature superconductor (HTS) striated tapes.